From Third World to first the Singapore story, 1965-2000 - Kuan Yew, Lee (New York HarperCollins Publisher, 2000)
Few gave tiny Singapore much chance of survival when it was granted independence in 1965. How is it, then, that today the former British colonial trading post is a thriving Asian metropolis with not only the world's number one airline, best airport and busiest port of trade, but also the world's fourth highest per capita real income?. The Story of that transformation is told here by Singapore's charismatic, controversial founding father, Lee Kuan Yew. Rising from a legacy of divisive colonialism, the devastation of the second World War, and general poverty and disorder following the withdrawal of foreign forces, Singapore is now hailed as a city of the future. This miraculous history is dramatically recounted by the man who not only lived through it all but who fearlessly forged ahead and brought about most of these changes. While Lee has been praised and vilified in equal measure for more than three decades, he has established himself as a force impossible to ignore in Asian and international politics. From Third World to First offers readers a compelling glimpse into this visionary's heart, soul and mind.
Includes Index
Keywords: Singapore-Economic Conditions, Singapore-Social Conditions Singapore-History 1965-1990